PENGGUNAAN RESOLUSI OLEH DK PBB UNTUK MEMAKSA IRAN MENYETUJUI INSPEKSI IAEA TERHADAP FASILITAS NUKLIR DI PARCHIN - Rahadyan Bhimantra, I Gusti Agung; Fasisaka, Idin; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2016)
ABSTRACT   The Iran’s nuclear development program got a serious attention from the IAEA for their improprieties in the conduct of Uranium enrichment and the involvement of the Iranian military at the Parchin site. As a result of Iran’s non-compliance to the IAEA, the UN Security Council had given some resolutions to Iran. These resolutions containing sanctions and provisions for Iran to obey and to give access to IAEA for an inspections at the Parchin site. The Security Council resolutions were a manifestation of the strength of an international organization. The Security Council sanctions have made significant impacts on Iran. The Iranian government reviewed their policy to cooperate and grant an access for IAEA to inspect the Parchin site. This study aims to describe the power of the UN Security Council as manifested in their resolutions to force Iran to give an access for IAEA inspections on Iran’s nuclear development facility in Parchin in 2012. This study assessed by using the theory of organizational architecture and two concepts; legal rational organization and the power of IOs. The locus of this study is from 2006 to 2012. Key Words: Iran's nuclear program, the UN Security Council Resolutions, organizational architecture, power of IOs